Assessing the effect of moderately increasing medium viscosity on the intrinsic dissolution rate and diffusion coefficient of ibuprofen particles - Marina Navas Bachiller; Tim Persoons; Anne-Marie Healy; Deirdre Maria D'Arcy (University of Huddersfield Press, 2022)
This study investigated the effects of moderately increasing medium viscosity through two viscosity enhancing agents (VEA) (HPMC and sucrose) on the intrinsic dissolution of a BCS class II drug (ibuprofen). The differences in intrinsic dissolution were characterized through the estimation of a diffusion coefficient (D) of ibuprofen in different media with the Levich equation. Increasing viscosity decreased the intrinsic dissolution rate of ibuprofen with both VEAs. The calculated D from intrinsic dissolution data overestimated the experimental value, but the results suggest that intrinsic dissolution could be used as a tool to estimate a relative change in D in different viscosities.